2016
DOI: 10.1016/j.jfluidstructs.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the effects of pitch-pivot-point location on the propulsion performance of a pitching airfoil

Abstract: a b s t r a c tAn experimental investigation was conducted to characterize the evolution of the unsteady vortex structures in the wake of a pitching airfoil with the pitch-pivot-point moving from 0.16C to 0.52C (C is the chord length of the airfoil). The experimental study was conducted in a low-speed wind tunnel with a symmetric NACA0012 airfoil model in pitching motion under different pitching kinematics (i.e., reduced frequency k ¼3.8-13.2). A high-resolution particle image velocimetry (PIV) system was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Therefore, the flapping-wing system is often simplified as a flapping foil, which is fixed in the uniform oncoming flow (Triantafyllou, Techet & Hover 2004). It is revealed that the thrust generation of a flapping foil is related to the formation of reverse von Kármán vortex streets (Godoy-Diana et al 2009), which is determined by multiple parameters, including the flapping frequency, the flapping amplitude, the flapping profile, the pitch-pivot-point location and the phase angle between heave and pitch motions (Read, Hover & Triantafyllou 2003;Hover, Haugsdal & Triantafyllou 2004;Tuncer & Kaya 2005;Tian et al 2016;Mackowski & Williamson 2017;Dash et al 2018;. Based on parametric studies of a fixed flapping foil, some scaling laws have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the flapping-wing system is often simplified as a flapping foil, which is fixed in the uniform oncoming flow (Triantafyllou, Techet & Hover 2004). It is revealed that the thrust generation of a flapping foil is related to the formation of reverse von Kármán vortex streets (Godoy-Diana et al 2009), which is determined by multiple parameters, including the flapping frequency, the flapping amplitude, the flapping profile, the pitch-pivot-point location and the phase angle between heave and pitch motions (Read, Hover & Triantafyllou 2003;Hover, Haugsdal & Triantafyllou 2004;Tuncer & Kaya 2005;Tian et al 2016;Mackowski & Williamson 2017;Dash et al 2018;. Based on parametric studies of a fixed flapping foil, some scaling laws have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the three dimensionless parameters discussed above, LEV development has also been characterized using other dimensionless parameters (Anderson et al 1998;Read, Hover & Triantafyllou 2003;Yu, Wang & Hu 2013;Tian et al 2016). Furthermore, Dabiri (2009) introduced the optimal vortex formation time to predict the LEV detachment time.…”
Section: Introductionmentioning
confidence: 99%
“…1998; Read, Hover & Triantafyllou 2003; Yu, Wang & Hu 2013; Tian et al . 2016). Furthermore, Dabiri (2009) introduced the optimal vortex formation time to predict the LEV detachment time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tian et al 23 performed experiments in a closed-circuit low-speed wind tunnel with a symmetric NACA 0012 airfoil model undertaking a sinusoidal pitching motion with 5 pitching amplitude at zero mean angle of attack and at Re ¼ 3400. The pitchpivot-point location was changed from 0.16c to 0.52c with the reduced frequency of the pitching motion ranged from k ¼ 3.8 to 13.2.…”
Section: Introductionmentioning
confidence: 99%